Lobaplatin-Induced Apoptosis Requires p53-Mediated p38MAPK Activation Through ROS Generation in Non-Small-Cell Lung Cancer - Zhang, Hongming; Chen, Runzhe; Wang, Xiyong; Zhang, Haijun; Zhu, Xiaoli; Chen, Jibei (Frontiers in Oncology, 2019)
Platinum-based chemotherapy is recommended as the first-line treatment regimen for patients with advanced non-small-cell lung cancer (NSCLC). Lobaplatin (LBP), a third-generation platinum anti-neoplastic agent, has shown an improved efficacy. This study is aimed to investigate the mechanisms of LBP-induced apoptosis in the A549 p53 wild-type cell line. The Cell Counting Kit-8 assay (CCK-8), flow cytometry (FCM), Western blot, xenograft tumor models, terminal deoxynucleotide transferase dUTP nick end labeling (TUNEL), and RNA interference were used in this study. Our results showed that the proliferation of A549 cells could be inhibited by LBP. At lower concentrations, LBP triggered cell cycle arrest at the G1 phase in A549 cells. LBP could also induce apoptosis of A549 cells. LBP also increased the expression of PARP and Bax and the cleavage of caspase-3, caspase-8, and caspase-9 and reduced Bcl-2 expression. In vivo experiment confirmed that LBP could inhibit tumor growth in the A549 xenograft models and induce apoptosis. Apoptosis of A549 cells was decreased after transfected with p53 shRNA or treated with reactive oxygen species inhibitor NAC and p38MAPK inhibitor SB203580, suggesting that the p53/ROS/p38MAPK pathway appeared to mediate the LBP-induced apoptosis of A549 cells. Our data demonstrate that LBP could be a promising candidate for the treatment of NSCLC with wild-type p53.